ANALISIS PERGESERAN LEMPENG BUMI YANG MENINGKATKAN POTENSI TERJADINYA GEMPA BUMI DI PULAU LOMBOK - Yanita Syafitri; Bahtiar Bahtiar; Lalu A. Didik (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2019)
This research is a qualitative research. Where the purpose of this research is to find out how the shifts of the earth’s plates around Lombok Island can increase the frequency of potential earthquakes on Lombok Island. This study uses a qualitative approach by paying attention to the theory of earth’s plates and the movements of the earh’s plates that have been described previously. The results of this study indicate a link between earth plate shifts and the frequency of earthquakes on Lombok Island. The world’s active tectonic plates in which the movements of two of them (the Indo-Australian Plate and the Eurasian Plate) greatly affect the frequency of earthquakes due to passing through Lombok Island. In addition to the two active tectonics plates of the world, there is also one Fault namely the Flores Up Fault which stretches from Flores to Lombok Island which forms a trough amd is very active.